Deterministic Network Model Revisited: An Algebraic Network Coding Approach - Erez, Elona; MinJi Kim; Yun Xu; Yeh, Edmund M.; Medard, Muriel (IEEE transactions on information theory, 2014)
The capacity of multiuser networks has been a long-standing problem in information theory. Recently, Avestimehr et al. have proposed a deterministic network model to approximate multiuser wireless networks. This model, known as the ADT network model, takes into account the broadcast nature as well as the multiuser interference inherent in the wireless medium. For the types of connections we consider, we show that the results of Avestimehr et al. under the ADT model can be reinterpreted within the algebraic network coding framework introduced by Koetter and Médard. Using this framework, we propose an efficient distributed linear code construction for the deterministic wireless multicast relay network model. Unlike several previous coding schemes, we do not attempt to find flows in the network. Instead, for a layered network, we maintain an invariant where it is required that at each stage of the code construction, certain sets of codewords are linearly independent.